Mechanically Superior Molybdenum Rhenium (MoRe®) Alloy provides an advanced option for Foot and Ankle Implants. Issue 3 (14th September 2018) - Parekh, Selene; Adams, Samuel; Nunley, James; Easley, Mark; Pedowitz, David; Hyer, Christopher; Brigido, Stephen
Category: Other Introduction/Purpose: One of the most common complications in orthopaedic surgery of the foot and ankle is nonunion or delayed union and bone or implant fractures. Although foot and ankle surgery has improved dramatically over the past decades primarily due to the development of better techniques, little progress has been made in the development of new materials for implants. Titanium, the most commonly used alloy for foot and ankle implants, has limited strength and is notch-sensitive so repetitive stress leads to fatigue failure of implants and limits design options. Better materials with optimized biomechanical properties could result in the development of superior foot and ankle implants and surgical techniques. The mechanical properties of Molybdenum-Rhenium (MoRe®), a promising new alloy for foot and ankle implants were tested. Methods: Standard test methods (ASTM 1717) were performed to evaluate the mechanical properties of Molybdenum Rhenium (MoRe®) alloy compared to Titanium (Ti-6Al-4 V, ASTM F136-13 annealed bar, Ti-ELI). Results: MoRe® is composed purely (99.99%) of molybdenum and rhenium and does not contain Nickel. Molybdenum is found in food and is a cofactor to the enzymes xanthine oxidase and sulfite oxidase, which are essential to bone and connective tissue metabolism. Rhenium is an inert metal with no biological affect. Mechanical testing showed MoRe to be superior to Titanium: Yield Strength: MoRe® 280ksi, Titanium 115ksi, Ultimate Tensile Strength: MoRe® 300ksi, Titanium 125 ksi. Elongation and Reduction in Area: MoRe® 13%, 50%, respectively; Titanium 10%, 25%. Recoil: MoRe® <2%, Titanium 6%. Hardness Range: MoRe® 280-800HV, Titanium 350-400HV. Max Run-Out Load Bent Rod: MoRe® 4.0 mm rod 350 N, Titanium 5.5 mm rod 150 N. Decrease in Max Run-Out Load Bent, Unbent, Re-bent Rod: MoRe® -9%, Titanium -17%. Conclusion: The MoRe® alloy, with its advantageous mechanical properties, offers great promise for the design of a new generation of smaller, stronger and more fatigue resistant foot and ankle implants, resulting in less soft tissue disruption, quicker recovery and better outcomes for patients.